DATABASES OF INTERMEDIARY ORGANIZATIONS AS A UNIFIED SOURCE OF STATISTICAL INFORMATION - Korepanov, George (Social Economics, 2018)
It has been determined that intergovernmental organizations (IGOs) play a key role in the international system, in the process of globalization they are gaining increasing importance. It has been pointed out that in recent decades there has been a large number of intergovernmental organizations that focus on diverse areas such as economics, education, culture, security, health and the environment, political science, and many others. Detailed information on intergovernmental organizations from 300 countries and territories, including intergovernmental and international non-governmental organizations (INGOs), contains the Yearbook of International Organizations, the Yearbook of International Organizations. It has been determined that most of the IGOs were created for economic purposes, namely, regulation of trade, financial markets and development projects. Based on the data of the Yearbook of international organizations, the distribution of the number of IGOs by types (B, C, D, E, F and G) and the main interests (security, economy, health and environment) are analyzed. It is proved that the number of IGOs, which are mainly focused on economic activity, is the largest in all types of organizations. It is indicated that in recent years, intergovernmental organizations have implemented the latest concepts of storage and analysis of statistical information in the form of databases that use innovative, promising technical software tools for their implementation. The available information resources of intergovernmental organizations are generalized and systematized, the main components of selected statistical databases are described.